Optical appearance and shadow of Kalb–Ramond black hole: effects of plasma and accretion models - Mou Xu; Ruonan Li; Jianbo Lu; Shining Yang; Shu-Min Wu (European Physical Journal C: Particles and Fields)
Abstract In this paper, we study the effect of the presence of plasma and different accretion models on the shadow and optical appearance of static spherically symmetric black holes containing the Kalb– field. We derive the motion equations for photons around the Kalb–Ramond black hole and constrain the Lorentz symmetry breaking parameters $$λ $$ λ and $$γ $$ γ using observational data released by the Event Horizon Telescope collaboration. The results indicate that, under the static spherical accretion model, as $$λ $$ λ or $$γ $$ γ increase, the peak value of the observed intensity for Kalb–Ramond black holes is enhanced and consistently exceeds that of the corresponding Schwarzschild black holes. In the presence of plasma, we find that as the plasma frequency increases, the photon sphere radius increases, whereas the black hole shadow radius decreases. In addition, compared to inhomogeneous plasma, the effect of homogeneous plasma on these features is more significant. Specifically, when the plasma is homogeneous, an increase in plasma frequency further enhances the observed intensity peaks. This suggests that the shadow of the Kalb–Ramond black hole is brighter due to the presence of plasma. Additionally, for the same Kalb–Ramond black hole model parameters and plasma frequency, the shadow of the Kalb–Ramond black hole in inhomogeneous plasma is larger than in the case of homogeneous plasma. Under the thin disk accretion model, an increase in the Lorentz symmetry breaking parameters decreases the observed intensity peak and increases the thickness of the photon ring and the lensed ring. The presence of plasma significantly alters the optical appearance of Kalb–Ramond black hole, providing a possible way to distinguish Kalb–Ramond black hole from Schwarzschild black hole.